PRMTs and miRNAs: functional cooperation in cancer and beyond. Issue 15 (3rd August 2019) - Jin, Jiamin; Martin, Matthew; Hartley, Antja-Voy; Lu, Tao
ABSTRACT: Epigenetic modulators play pivotal roles in directing gene expression for the maintenance of normal cellular functions. However, when these modulators are aberrantly regulated, this can result in a variety of disease states, including cancer. One class of epigenetic regulators, protein arginine methyltransferases (PRMTs), have been shown to play critical roles in disease through methylation of arginine residues (R) on histone or non-histone proteins. Quite different from PRMTs, microRNAs (miRNAs) belong to the family of modulators known as noncoding RNAs (ncRNA) that act to regulate gene expression via RNA-mediated gene silencing. Importantly, miRNAs are frequently dysregulated and contribute to the progression of cancer and other conditions, including neurological and cardiovascular diseases. Recently, numerous studies have shown that miRNAs and other epigenetic enzymes can co-regulate each other. This review highlights multiple nodes of interaction between miRNAs and PRMTs and also discusses how this interplay might open up promising opportunities for drug development for the treatment of cancer and other diseases.